1994
DOI: 10.1210/jcem.78.1.8288693
|View full text |Cite
|
Sign up to set email alerts
|

Absence of p53 point mutations in parathyroid adenoma and carcinoma.

Abstract: Primary hyperparathyroidism is a common disorder characterized by aberrant growth and function of solitary or multiple parathyroid glands. Many, if not all, parathyroid adenomas are examples of benign clonal neoplastic growth. The molecular events associated with the development of parathyroid neoplasia have not been well characterized. We examined benign and malignant parathyroid tissues for structural abnormalities of the p53 tumor suppressor gene. To screen for mutations in the p53 gene, we analyzed polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…TP53 gene mutations are among the most common genetic aberrations in malignant epithelial tumors, although these genetic events seem to be unusual in parathyroid carcinomas [103][104][105]. Even so, LOH of one TP53 allele seems to be more common [103].…”
Section: Somatic Genetics In Parathyroid Carcinomasmentioning
confidence: 99%
“…TP53 gene mutations are among the most common genetic aberrations in malignant epithelial tumors, although these genetic events seem to be unusual in parathyroid carcinomas [103][104][105]. Even so, LOH of one TP53 allele seems to be more common [103].…”
Section: Somatic Genetics In Parathyroid Carcinomasmentioning
confidence: 99%
“…As noted above, CCND1 gene amplification (Zhao et al 2014, Pandya et al 2017 and cyclin D1 overexpression (Vasef et al 1999, Zhao et al 2014 are frequently observed in parathyroid cancer. Several additional studies sought to interrogate candidate genes for sequence and/or expression abnormalities in parathyroid cancer, showing that such important human cancer genes as p53 (Cryns et al 1994b, Hakim & Levine 1994, RB1, BRCA2 (Shattuck et al 2003b), and others (Yoshimoto et al 1992, Cryns et al 1994a were unlikely to make a major contribution. The absence of alterations in such common 'cancer genes' was further confirmed by next-generation sequence analyses (Kasaian et al 2013, Yu et al 2015, Pandya et al 2017.…”
Section: Additional Genetic Considerationsmentioning
confidence: 99%
“…As pathogenetic factors of parathyroid adenomas, the rearrangement and overexpression of the PRAD1/cyclin D1 gene, a cell cycle regulator, and loss of chromosome 11 DNA sequences usually including the postulated region of MEN-I gene have been noted [29 -31]. Inactivation of the retinoblastoma (RB) tumor suppressor gene, which normally inhibits progression through the cell cycle at the G 1 /S transition and P53 tumor suppressor gene abnormalities in parathyroid carcinoma, has been demonstrated [32][33][34].…”
Section: Et Al Analyzed the Clonality Ofmentioning
confidence: 99%